Morningness and academic burnout among university students: the mediating role of procrastination - İsmail Önder; Ayşe Nesibe Önder; Ezgi Güven Yıldırım (BMC Psychology)
Abstract Background Morningness-eveningness preference, which is an individual difference, is associated with the academic burnout of university students. In addition, academic procrastination is common among university students, and students who procrastinate experience more anxiety, stress, and negative thoughts. Therefore, academic procrastination may mediate the relationship between morningness and academic burnout. Methods This study examines the effects of academic procrastination and morningness on academic burnout and explores the mediating role of academic procrastination in the relationship between morningness and burnout. A total of 558 university students participated in the study. A total of 119 of these students were male, and 439 were female. The ages of the students ranged from 18 to 22 years. Results Female students had higher exhaustion scores than male students did, and freshman students had higher morningness scores than both sophomore and junior students did. The relationships between all the variables examined were significant. The mediation analyses revealed that procrastination has a partial mediating role in the relationship between the morningness and burnout dimensions. Conclusions The results of this study suggest that procrastination may help explain some of the links between morningness and burnout. Avoiding the procrastination tendencies of individuals, especially those who are evening-type, may be associated with lower levels of academic burnout, though causality cannot be confirmed due to the cross-sectional nature of the study.